Development Of Learning Based Teaching Materials On Quadratic Function Materials To Improve Students' Mathematical Representation Skills - Ulfa Luthfiani; Sehatta Saragih; Elfis Suanto (JTMT: Journal Tadris Matematika, 2025)
This research aims to develop discovery learning-based teaching materials on quadratic functions to improve mathematical representation abilities of grade X students. The low mathematical representation ability of Indonesian students reflected in TIMSS 2015 results is the research background. Research and Development (R&D) methodology with a 4D model (Define, Design, Develop, Disseminate) was used to develop the learning product. Validation was conducted by three mathematics education experts, practicality testing through student response questionnaires, and effectiveness was measured using a Post-test Only Control Group design comparing experimental and control classes. The findings showed very high validity at 91.54%, practicality reached 79.31% in the practical category, and significant effectiveness demonstrated through average score increase from 73.27 to 83.20 (sig = 0.000 < 0.05). The Z proportion test yielded 1.8974 > 1.645, indicating more than 75% of students achieved the minimum mastery standard. This teaching material successfully facilitates mathematical representation skill development through structured discovery activities, although visual representation aspects need further optimization. The discovery learning approach effectively optimizes students' knowledge construction through meaningful learning experiences while overcoming conventional learning limitations in developing mathematical representation competencies